Screening of the Squint among Residents Visiting a Tertiary Care Hospital in Uttarakhand - Vatsala Vats; Divija Arora; Priyanka Gupta (Journal of Epidemiology and Public Health, 2024)
Background: Squint is also known as Strabismus and includes Latent and Manifest varieties. It contributes to childhood visual impairment and amblyopia, adding to the stress of loss of functional vision. The regular surveys of such entities help to assess the magnitude, and measures needed for prophylaxis and treatment. The aim of the study is a screening of the Squint among residents visiting a tertiary care hospital in Uttarakhand.Subjects and Method: This was a cross-sectional hospital-based study conducted over a period of one year at Shri Mahant Indiresh Hospital, Shri Guru Ram Rai Institute of Medical and Health Sciences, Dehradun. A total of 100 patients who found with tropias and phobias were further evaluated to provide them with the correct diagnosis and optimum guidance regarding management. The variables of this study were a demographic profile, Age, Gender, type of squint, convergence insufficiency, power of convergence, and prevalence of squint. SSPS was used to assess the data. A p<0.005 was suggestive of significance.Results: Out of a total of 4,280 patients, 2,240 (52.28%) were males, 2,044 (47.71%) were females, 100 (2.3%) cases were found to be of horizontal tropias, while Convergence Insufficiency (CI) was noted in 720 (16.8%). Esotropia was more common (65%) than Exotropia and the difference was statistically significant with a p-value less than 0.001. The common feature of both the exotropia and esotropia was the age of presentation which was 11 to 15 years. While the age group with the majority of cases CI (16.8%) was between 5 to 10 years.Conclusion: This study the magnitude and distribution of strabismus and CI in the region. It also helps to understand the importance of timely assessment and management for the optimum growth and development of an informed individual and community. Keywords: Strabismus, convergence, prevalence